CFD and experimental analysis of the coolant flow in cryogenic milling. (May 2019) - Tahmasebi, Ehsan; Albertelli, Paolo; Lucchini, Tommaso; Monno, Michele; Mussi, Valerio
Abstract: Cryogenic cooling could improve the machining performance for hard-to-cut materials. Deployment of this modern technology for milling applications, specifically because of their severe working conditions and complicated physical phenomena inside cryogenic fluids, requires further research to become credible for industrial applications. Obtaining accurate models for coolant behavior is essential for optimum design, prediction of operational limits, and safe control of the cooling process. In this paper, Computational Fluid Dynamics (CFD) were used to determine the behavior of the liquid nitrogen (LN2 ) inside the coolant delivery system and the interaction of the coolant jet with the cutting area. The role of working conditions as well as nozzle geometry, formation of cavitation inside the tool, coolant pressure, and wall temperature on the efficiency of the coolant delivery were investigated in this study. Initial experimental flow measurements were used to predict the simulation setup and evaluate the results. Experimental milling tests were performed to verify the numerical findings. Cutting forces, coolant mass flow rate, temperature, and pressure were measured during the tests. A mechanistic cutting force model and the morphology of the chips were used to interpret the effect of liquid nitrogen on the cutting mechanisms. Results of this study offer three main suggestions for reliable industrial cryogenic milling: using liquid nitrogen in the range of 2–4 bar, improving the insulation of the feeding line and finding a technical solution for non-insulated parts, and increasing the quality of the liquid in the coolant mixture close to the milling head. Outcomes of this study could help to improve the cooling performance and implement a reliable industrial solution for cryogenic milling. Highlights: Effect of working conditions and geometry on performance of the cooling system. Role of cavitation and fluid pressure on efficiency of the coolant feeding system. Estimating the distribution of the coolant over the machining zone. Importance of the isolation and cool-down process on cryogenic liquid quality and consequently reliable cooling. Using the coolant in a low pressure range (2–4 bar in this study) shows promising results for efficient cooling.